Sistem: x+y+z=d, y+z+t=a, z+t+x=b, t+x+y=c

Adderall

New member
Joined
Feb 18, 2017
Messages
9
I tried a lot, but i don't know how to solve this sistem:

x+y+z=d
y+z+t=a
z+t+x=b
t+x+y=c

The answer is: x=1/3(-2a+b+c+d), y=1/3(a-2b+c+d, t=a+b+c-d;

Thank you very much !
 
Let's rewrite the system of equations as follows:

\(\displaystyle 1x+1y+1z+0t=d\)

\(\displaystyle 0x+1y+1z+1t=a\)

\(\displaystyle 1x+0y+1z+1t=b\)

\(\displaystyle 1x+1y+0z+1t=c\)

Next, let's express this system of equations as an augmented matrix:

\(\displaystyle \left[\begin{array}{cccc|c}1 & 1 & 1 & 0 & d \\ 0 & 1 & 1 & 1 & a \\ 1 & 0 & 1 & 1 & b \\ 1 & 1 & 0 & 1 & c \end{array}\right]\)

Now we may use row operations to convert the matrix into reduced row echelon form, a process called Gauss–Jordan elimination.

Now, if we perform the row operation:

\(\displaystyle R_1-2R_2+R_3+R_4\)

We obtain:

\(\displaystyle \left[\begin{array}{cccc|c}3 & 0 & 0 & 0 & -2a+b+c+d \\ 0 & 1 & 1 & 1 & a \\ 1 & 0 & 1 & 1 & b \\ 1 & 1 & 0 & 1 & c \end{array}\right]\)

Next, performing the row operation:

\(\displaystyle \displaystyle \frac{1}{3}R_1\)

We obtain:

\(\displaystyle \left[\begin{array}{cccc|c}1 & 0 & 0 & 0 & \dfrac{-2a+b+c+d}{3} \\ 0 & 1 & 1 & 1 & a \\ 1 & 0 & 1 & 1 & b \\ 1 & 1 & 0 & 1 & c \end{array}\right]\)

Next, we perform the row operation:

\(\displaystyle R_2-R_3+R_1\)

And we have:

\(\displaystyle \left[\begin{array}{cccc|c}1 & 0 & 0 & 0 & \dfrac{-2a+b+c+d}{3} \\ 0 & 1 & 0 & 0 & \dfrac{a-2b+c+d}{3} \\ 1 & 0 & 1 & 1 & b \\ 1 & 1 & 0 & 1 & c \end{array}\right]\)

Can you continue?
 
Ah, poor z. It never gets any respect.

If you don't like using matrices, here is a more "basic" way of doing the same thing:

You have the equations
x+ y+ z= d
y+ z+ t= a
z+ t+ x= b
t+ x+ y= c
Four equations in four unknowns (I presume that a, b, c, and d are "given" numbers and that x, y, z, and t are the "unknowns" we are to solve for.)

We start by "eliminating" one unknown at a time. I will, pretty arbitrarily, start by eliminating t. Subtracting the third equation from the second, -x+ y= a- b. Subtracting the fourth equation from the third -y+ z= b- c.

Since there was no t in the first equation we now have
x+ y+ z= d
-x+ y= a- b
-y+ z= b- c Three equations in three unknowns.

Now eliminate z by subtracting the third of these equations from the first: x+ 2y= d- b+ c

Since there was no z in the second equation we now have
x+ 2y= d- b+ c
-x+ y= a- b Two equations in two unknowns.

Now we can eliminate x by adding those two equations:
3y= a- 2b+ c+ d. One equation in one unknown.

We can solve that last equation for y by dividing both sides by 3.

Then "back substitute" that value of y in either of the two equations, x+ 2y= d- b+ c or -x+ y= a- b, to get an equation to solve for x.

Then substitute those two values for x and y in any of the previous three equations to get an equation to solve for z.

Finally, substitute those values for x, y, and z into any of the four original equation to get an equation to solve for t.
 
Last edited:
Top